Analisis Pengawasan Inspektur Angkutan Udara Kantor Otoritas Bandar Udara Wilayah I Kelas Utama terhadap Penetapan Harga Tarif Tiket oleh Maskapai PT. Lion Mentari Airlines - Ridho, Nofah; Kusuma, Nur Makkie Perdana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In domestic flights, currently many people choose economic services, of course this is a very competitive aviation business arena for users of aviation services in terms of fares, equipment, services, human resources, and flight security and safety. This study aims to determine the setting of tariffs, besides that this research also aims to determine the supervision of tariff implementation. Air Transport Inspector. This research uses a type of qualitative descriptive research method. To get answers from the research, the researcher made a research design in the form of observations, interviews, and documentation. The data obtained is in the form of interview results with the Air Transport Inspector at the Regional 1 Main Airport Authority Office. The results of the study show that the arrangements made by the Ministry of Transportation are the main basis for Aviation Business Entities in setting fares and facilitating supervision for Air Transport Inspectors. Fare inspection supervision is an SOP given by the Ministry of Transportation to Air Transport Inspectors. Not only that, tariff monitoring can occur when there are public reports and national holidays. Existing obstacles such as the occurrence of violations can be handled by a Ministerial Decree in accordance with the rules for enforcing sanctions. Keywords : tariff, policy, supervision, sanctions.